Comparison of plasminogen activator inhibitor-1 levels in chronic hepatitis B patients with hepatic cirrhosis and without hepatic cirrhosis - Hamdany, Andhika Kusuma; Parewangi, Muhammad Luthfi; Saleh, Sahyuddin; Bakri, Syakib; Akil, Fardah; Abadi, Satriawan; Seweng, Arifin (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: One of the hepatic cirrhosis manifestations is bleeding disorders. Among all the substance that plays a pivotal role in maintaining the balance between thrombosis and thrombolysis is PAI-1, synthesized by hepatocytes. The dynamics of increase and decrease of PAI-1 is a natural response to the ongoing hepatic cirrhosis, but may not be seen in non-hepatic cirrhosis. PAI-1 levels also depends on the stage of fibrosis. Several conditions may interfere with PAI-1 levels including age, body mass index, and gender Objectives: This study aims to find out the comparison of PAI-1 levels in hepatitis B patients with hepatic cirrhosis and without hepatic cirrhosis and to compare it with every stage of hepatic cirrhosis. Patients and Methods: This study is an observational analytical study with a cross-sectional approach conducted at Wahidin Sudirohusodo hospitals, Makassar. Subjects are chronic hepatitis B patients with and without hepatic cirrhosis which meet inclusion criteria. Serum PAI-1 levels were measured by using Bender MedSystems human plasminogen activator inhibitor-1 ELISA kit (BMS2033) and using the ELISA technique. Statistical analysis was performed using the Kolmogorov Smirnov normality test as well as the Mann-Whitney method. Statistical results are considered significant if the p-value <0.05. Results: The research was conducted on 60 subjects who meet inclusion criteria, consisting of 33 men and 27 women. There were 16 patients with hepatic cirrhosis. Levels of PAI-1 in hepatic cirrhosis was significantly different which lower than non-hepatic cirrhosis patient (0.43 ng/mL Vs 1.11 ng/mL, p=0.024). By staging of hepatic fibrosis, stage F2 hepatic fibrosis had the highest levels of PAI-1, in contrast with end-stage hepatic fibrosis which had the lowest levels. Conclusion: Levels of PAI-1 fluctuate through different stages of hepatic fibrosis. The significant difference in PAI-1 levels in hepatic cirrhosis and non-hepatic cirrhosis demonstrates a correlation between PAI-1 and hepatic cirrhosis Keywords: Chronic hepatitis B, Hepatic cirrhosis, Plasminogen Activator Inhibitor-1